IMPLEMENTASI KEBIJAKAN PRINSIP - PRINSIP PELAYANAN PUBLIK PADA UNIT PELAKSANA TEKNIS PENYEBERANGAN ATANJUNG API-API DINAS PERHUBUNGAN KABUPATEN BANYUASIN PROVINSI SUMATERA SELATAN - Yofitri Heny Wahyuli (STIA Bengkulu, 2024)
The main objective of this research is to find out and analyze the implementation of public service principles in the technical implementation unit for the White Water crossing of the Bengkalis Regency Transportation Service. The type of research used in this research is qualitative using descriptive surveys and Miles and Huberman data reduction techniques. There were 10 informants in this research with the Head of UPT as the key informant. Data collection techniques using interviews and descriptive data analysis using a qualitative approach. The main conclusion of this research states that the Implementation of Public Service Principles at the Tanjung Api-api Crossing Technical Implementation Unit of the Banyuasin Regency Transportation Service is quite implemented, but services still need to be improved and improved based on indicators of Communication, Resources, Disposition and Bureaucratic Structure.